Management of pulmonary hypertension in neonates with congenital diaphragmatic hernia - Vijfhuize, Sanne; Schaible, Thomas; Krämer, Ulrike (European journal of pediatric surgery, 2012)
Pulmonary hypertension associated with congenital diaphragmatic hernia is still one of the major challenges in neonatal intensive care units. Several relevant pathways in its pathogenesis have been described and studied, but the absence of well-designed randomized controlled trials and the scattered data on the pharmacokinetics and pharmacodynamics of most of the drugs used in these patients hamper progress significantly. This review aims to give an overview of current management strategies in the antenatal and neonatal phase, and provides founded clinical recommendations.